W kierunku wspólnej przestrzeni administracyjnej – wpływ dorobku Rady Europy na krajowe systemy prawa - Dąbrowska, Anna (PRAWO i WIĘŹ, 2025)
This article analyzes the mechanisms through which the Council of Europe’s acquis influences the development of national administrative law systems in Europe and evaluates the process of forming a common European administrative space. The author employed a dogmatic-exegetical method to analyze the Council of Europe’s normative documents, a legal functionalism method to identify procedural standards developed by the European Court of Human Rights, and a comparative method enabling comparison of reception and implementation mechanisms in selected Western and Central-Eastern European legal systems. The analysis demonstrated that Council of Europe standards, despite their often non-binding character, effectively shape a common administrative space through two principal mechanisms – judicial reception and direct legislative implementation. A pivotal role is played by Strasbourg jurisprudence, recommendations of the Council of Europe’s Committee of Ministers, and opinions of the Venice Commission. In conclusion, the article proposes directions for de lege ferenda reforms of the Polish administrative law system, including constitutional recognition of the right to good administration, digital modernization of procedures, and strengthening guarantees of fair administrative proceedings.